2019
DOI: 10.1093/mnras/stz1849
|View full text |Cite
|
Sign up to set email alerts
|

Bias and robustness of eccentricity estimates from radial velocity data

Abstract: Eccentricity is a parameter of particular interest as it is an informative indicator of the past of planetary systems. It is however not always clear whether the eccentricity fitted on radial velocity data is real or if it is an artefact of an inappropriate modelling. In this work, we address this question in two steps: we first assume that the model used for inference is correct and present interesting features of classical estimators. Secondly, we study whether the eccentricity estimates are to be trusted wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 78 publications
0
39
0
Order By: Relevance
“…The residuals of the nine-signals model plus white noise fit have a root mean square (RMS) of 3.1 m s −1 , which is higher than the nominal uncertainties of the SOPHIE data (1.2 m s −1 ). We studied the residuals with the methods of Hara et al (2019) and found that they are temporally correlated, which, if not accounted for, might corrupt the orbital element estimates. In Appendix E, we show that a consistent model of the data can be obtained with a noise model that includes white and correlated components.…”
Section: Radial Velocities Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The residuals of the nine-signals model plus white noise fit have a root mean square (RMS) of 3.1 m s −1 , which is higher than the nominal uncertainties of the SOPHIE data (1.2 m s −1 ). We studied the residuals with the methods of Hara et al (2019) and found that they are temporally correlated, which, if not accounted for, might corrupt the orbital element estimates. In Appendix E, we show that a consistent model of the data can be obtained with a noise model that includes white and correlated components.…”
Section: Radial Velocities Analysismentioning
confidence: 99%
“…(i) None of these periods clearly appear in the bisector span, log R hk , or photometry. (ii) While eccentric planets can be mistaken for planet pairs near a 2:1 MMR, they are very unlikely to appear as planets near a 3:2 resonance (Hara et al 2019). (iii) The periods could be due to instrument systematics.…”
Section: Periodicity Originmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a night binning of the dataset, as suggested in Dumusque et al (2012). This simple strategy has proved to be efficient to reduce the effect of short-term correlated noises on orbital elements (e.g., Hara et al 2019). In total, 145 individual measurements were available.…”
Section: Harpsmentioning
confidence: 99%
“…The first arises from the fact that eccentricity is a positive-definite quantity: it cannot be negative. Therefore, the fitted eccentricities for planets on circular or low-eccentricity orbits are biased towards higher values (Lucy & Sweeney 1971;Shen & Turner 2008;Zakamska et al 2011;Hara et al 2019). For example, Zakamska et al (2011) show that the fraction of low eccentricity systems could be underestimated by as much as a factor of 3.…”
Section: Rv Mischaracterization Of Planet Eccentricitymentioning
confidence: 99%